Serum mesothelin for early detection of asbestos-induced cancer malignant mesothelioma - Creaney, J.; Olsen, N.; Brims, Fraser; Dick, I.; Musk, A.; De Klerk, N.; Skates, S.; Robinson, B. (American Association for Cancer Research Inc, 2010)
Background: Malignant mesothelioma is an aggressive, almost uniformly fatal tumor, primarily caused by exposure to asbestos. Since the recent discovery that serum mesothelin is a sensitive and highly specific biomarker for mesothelioma, one of the key issues raised is whether mesothelin levels represent a useful screening test for asbestos-exposed at-risk individuals. In this study, soluble mesothelin was determined in sequential serum samples collected from asbestos-exposed individuals before the development of mesothelioma. Methods: Archival serum samples from 106 individuals who developed mesothelioma, 99 asbestosexposed individuals from the Wittenoom Cancer Surveillance Program, and 109 non-asbestos-exposed individuals from the Busselton Health Survey were identified. Serum mesothelin concentrations were determined using the MESOMARK assay. Results: Longitudinal mesothelin levels determined in healthy asbestos-exposed individuals over a period of 4 years were stable (Pearson's r = 0.96; P < 0.0001). There was no correlation between mesothelin concentration and cumulative asbestos exposure. Mesothelin concentrations were greater than the threshold value of 2.5 nmol/L in the penultimate serum sample before the diagnosis of mesothelioma in 17 of 106 people. Using an increase above the 95% confidence interval of the mean of a given individual's longitudinal mesothelin results, 33 of 82 individuals had increasing mesothelin levels before diagnosis. Conclusion: In a population with a high pretest probability of developing mesothelioma, the serum biomarker mesothelin is elevated in absolute terms in 15% and in relative terms in 40% of the group. Impact: Future studies examining a combination of biomarkers could improve sensitivity of screening. ©2010 AACR.